TMEM70 mutations cause isolated ATP synthase deficiency and neonatal mitochondrial encephalocardiomyopathy - Cízková, Alena; Stránecký, Viktor; Mayr, Johannes A; Tesarová, Markéta; Havlícková, Vendula; Paul, Jan; Ivánek, Robert; Kuss, Andreas W; Hansíková, Hana; Kaplanová, Vilma; Vrbacký, Marek; Hartmannová, Hana; et al. (Nature genetics, 2008)
We carried out whole-genome homozygosity mapping, gene expression analysis and DNA sequencing in individuals with isolated mitochondrial ATP synthase deficiency and identified disease-causing mutations in TMEM70. Complementation of the cell lines of these individuals with wild-type TMEM70 restored biogenesis and metabolic function of the enzyme complex. Our results show that TMEM70 is involved in mitochondrial ATP synthase biogenesis in higher eukaryotes.
Keywords: mutace; Mitochondrial Encephalomyopathies; testy genetické komplementace; buněčné linie; novorozenec; transfekce; Transfection; lidé; kardiomyopatie; Infant, Newborn; mitochondriální encefalomyopatie; Genetic Complementation Test; mitochondriální proteiny; membránové proteiny; Mutation; komplementární DNA; Cell Line; Mitochondrial Proton-Translocating ATPases; Cloning, Molecular; Cardiomyopathies; Membrane Proteins; mitochondriální protonové ATPasy; klonování DNA; DNA, Complementary; Mitochondrial Proteins; Humans